2022
DOI: 10.1002/ps.7088
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive attributes and functional response ofAnastatus japonicuson eggs ofAntheraea pernyi, a factitious host

Abstract: BACKGROUND Anastatus japonicus Ashmead (Hymenoptera: Eupelmidae) is a solitary egg endoparasitoid that has been studied for inundative biological control of Halyomorpha halys Stål (Hemiptera: Pentatomidae) in China. In this study, we assessed the reproductive attributes and functional response of Anastatus japonicus on a factitious host, Antheraea pernyi (Guérin‐Méneville) (Lepidoptera: Anthelidae) at 25 ± 1 °C, 70 ± 5% relative humidity and 16 h:8 h light/dark photoperiod. RESULTS The mean lifetime fecundity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
3
5
1
Order By: Relevance
“…A study reported that the sex ratio of adult progeny of Anastatus japonicus was slightly male-biased (51.2%) when the parasitoids were reared on Antheraea pernyi. 34 Our results which showed a progeny sex ratio of 53.51% is consistent with that of this study.…”
Section: Discussionsupporting
confidence: 93%
“…A study reported that the sex ratio of adult progeny of Anastatus japonicus was slightly male-biased (51.2%) when the parasitoids were reared on Antheraea pernyi. 34 Our results which showed a progeny sex ratio of 53.51% is consistent with that of this study.…”
Section: Discussionsupporting
confidence: 93%
“…The reported oviposition period (30.17 days) and female adult longevity (45.17 days) of M. albitarsis in this study are consistent with a previous study 48 (actually M. albitarsis, but it was mistakenly identified as Anastatus albitarsis), 4 but the fecundity (330.90 offspring/female) of this parasitoid on COS eggs in this study was lower than that reported in the previous study (380.20 offspring/female). Mi et al 49 reported that A. japonicus produced 404.3 progeny on COS eggs during 42.3 days of the oviposition period; both the fecundity and the oviposition duration were slightly higher than found in this study (372.73 eggs/female, 38.74 days). When A. japonicus was reared on R. pedestris, it could parasitize only 15.65 host eggs and lived 31.36 days.…”
Section: Discussioncontrasting
confidence: 76%
“…However, there could also be costs associated with multiple mating in terms of energy demand and harassment by males, and all these factors could come at a cost to longevity and/or fecundity 45 . Although males were provided throughout the female's life span, mating might not occur or the mating rate likely decreased due to the weakness of the females in late life, as found in congeners parasitoids such as A. japonicus , A. orientalis and A. bifasciatus 12,42,43,49 . This suggests that provision of adult food could be essential for these parasitoids to prolong their life span and continuously produce eggs to parasitize their hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies concerning the ORs and IRs of parasitoid wasps are essential for understanding the mechanisms of the olfactory system that finds the host pests and for developing an olfactory-based integrated pest management (IPM) strategy. Previous research on A. japonicus focused primarily on its morphology, ecology, and raising [ 1 , 5 , 6 , 7 , 9 , 35 , 36 , 37 ]; little information is available on its chemosensory mechanisms. Two previous studies have reported transcriptome datasets from female A. japonicus antennae [ 38 , 39 ], but neither of these studies involved the female abdominal and male antennal transcriptomes.…”
Section: Introductionmentioning
confidence: 99%